Diagnostic accuracy of dermoscopy for onychomycosis: A systematic review - Lim, Sophie Soyeon; Hui, Laura; Ohn, Jungyoon; Cho, Youngjoo; Oh, Choon Chiat; Mun, Je-Ho (Frontiers in Medicine, 2022)
Background Dermoscopy is a non-invasive adjuvant diagnostic tool that allows clinicians to visualize microscopic features of cutaneous disorders. Recent studies have demonstrated that dermoscopy can be used to diagnose onychomycosis. We performed this systematic review to identify the characteristic dermoscopic features of onychomycosis and understand their diagnostic utility. Methods We searched the Medline, Embase, Scopus, and Cochrane databases from conception until May 2021. Studies on the dermoscopic features of onychomycosis were screened. The exclusion criteria were as follows: fewer than 5 cases of onychomycosis, review articles, and studies including onychomycosis cases that were not mycologically verified. Studies on fungal melanonychia were analyzed separately. We adhered to the MOOSE guidelines. Independent data extraction was performed. Data were pooled using a random effects model to account for study heterogeneity. The primary outcome was the diagnostic accuracy of the dermoscopic features of onychomycosis. This was determined by pooling the sensitivity and specificity values of the dermoscopic features identified during the systematic review using the DerSimonian-Laird method. Meta-DiSc version 1.4 and Review Manager 5.4.1 were used to calculate these values. Results We analyzed 19 articles on 1693 cases of onychomycosis and 5 articles on 148 cases of fungal melanonychia. Commonly reported dermoscopic features of onychomycosis were spikes or spiked pattern (509, 30.1%), jagged or spiked edges or jagged edge with spikes (188, 11.1%), jagged proximal edge (175, 10.3%), subungual hyperkeratosis (131, 7.7%), ruins appearance, aspect or pattern (573, 33.8%), and longitudinal striae (929, 54.9%). Commonly reported features of fungal melanonychia included multicolor (101, 68.2%), non-longitudinal homogenous pigmentation (75, 50.7%) and longitudinal white or yellow streaks (52, 31.5%). Conclusion This study highlights the commonly identified dermoscopic features of onychomycosis. Recognizing such characteristic dermoscopic features of onychomycosis can assist clinicians diagnose onychomycosis by the bedside.